Time domain identification of hybrid base isolation systems using free vibration tests. - Oliveto, Nicholas D. (Earthquake engineering & structural dynamics.)
A procedure for the dynamic identification of the physical parameters of coupled base isolation systems is developed in the time domain. The isolation systems considered include high damping rubber bearings (HDRB) and low friction sliding bearings (LFSB). A bi-linear hysteretic model is used alone or in parallel with a viscous damper to describe the behavior of the HDRB system, while a constant Coulomb friction device is used to model the LFSB system. After deriving the analytical dynamical solution for the coupled system under an imposed initial displacement, this is used in combination with the least-squares method and an iterative procedure to identify the physical parameters of a given base isolation system belonging to the class described by the models considered. Performance and limitations of the proposed procedure are highlighted by numerical applications. The procedure is then applied to a real base isolation system using data from static and dynamic tests performed on a building at Solarino. The results of the proposed identification procedure have been compared to available laboratory data and the agreement is within ±10%. However, the need for improvement both in models and testing procedures also emerges from the numerical applications and results obtained.